The empirical research of the factors determining the investment activity of Russian companies - ТепловаТамара Викторовна; КрыловаМ. С. (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
The article deals with the examination of some fundamental and specific determinants of the investment behavior of Russian companies. To investigate the investment behavior it is important to analyze three investment trends: 1) investments made in the modernization and expansion of the existing capital assets, represented as capital expenditure CAPEX; 2) financial investments made in the form of investitions in other companies. shares circulating on the market which allow to implement external growth strategies by means of integrated and conglomerate acquisition (Long Term Investment, LTI); 3) intellectual investments or investments in intellectual capital, which can be viewed as part of company capital assets. A number of questions arise when analyzing investment behavior determinants: 1) to what extent the regulatory function of the stock market is determinant and to what extent managers take into account the market forecast of investment opportunities; 2) to what extent managers take into account risk factors, whether they consider systematic risks only as it is recommended by the theory of finance, or regard an option to postpone investment projects in real assets; specific and branch risks are important; 3) to what extent the Russian market financial limitations restrain the market activity and investitions are sensitive to generated cash flows, and whether a holding system of diversified business is able to level out the problem of expensive external funds; 4) whether non-fundamental determinants (such as the structure of the holders and the board of directors, the age of the president and etc.) are important for making choice of investments in terms of time periods and directions. The article highlights both internal and external investment behavioral indicators available for an analyst which can be applied when doing research. It also suggests a model for eliciting investment behavioral factors and presents hypotheses of traditional fundamental factors impact: Tobin.s Q, profitability, availability of the operating cash flow, systematic and specific risks. It suggests risk metrication for the Russian market. The state share in the structure of ownership is considered as a non-fundamental factor. The empiric analysis of 28 major Russian companies over a five-year period has shown that finance and capital investments are exposed to various factors impact. Financial restraints affect real investments whose determinants are availability of own funds (high levels of accumulated cash flow, profitability, investment possibilities diagnosed by the stock market and the specific risk. Financial investments are more sensitive to the profitability of the last few years and systematic risk. What is more, the rise of risk stirs t interest to the share purchase in order to diversify capital.